Development of Lentiviral Vectors Simultaneously Expressing Multiple siRNAs Against CCR5, vif and tat/rev Genes for an HIV-1 Gene Therapy Approach - Francesca Spanevello; Arianna Calistri; Claudia Del Vecchio; Barbara Mantelli; Chiara Frasson; Giuseppe Basso; Giorgio Palù; Marina Cavazzana; Cristina Parolin (Elsevier, 2016)
Gene therapy holds considerable promise for the functional cure of HIV-1 infection and, in this context, RNA interference (RNAi)-based approaches represent powerful strategies. Stable expression of small interfering RNAs (siRNAs) targeting HIV genes or cellular cofactors has the potential to render HIV-1 susceptible cells resistant to infection. To inhibit different steps of virus life cycle, self-inactivating lentiviral vectors expressing multiple siRNAs targeting the CCR5 cellular gene as well as vif and tat/rev viral transcripts, under the control of different RNA polymerase III promoters (U6, 7SK, H1) were developed. The use of a single RNA polymerase III promoter driving the expression of a sequence giving rise to three siRNAs directed against the selected targets (e-shRNA) was also investigated. Luciferase assay and inhibition of HIV-1 replication in human Jurkat T-cell line were adopted to select the best combination of promoter/siRNA. The efficacy of selected developed combinatorial vectors in interfering with viral replication was evaluated in human primary CD4+ T lymphocytes. We identified two effective anti-HIV combinatorial vectors that conferred protection against R5- and X4- tropic viruses. Overall, our results showed that the antiviral effect is influenced by different factors, including the promoter used to express the RNAi molecules and the selected cassette combination. These findings contribute to gain further insights in the design of RNAi-based gene therapy approaches against HIV-1 for clinical application.